Child maltreatment and antisocial behaviour in the United Kingdom: Changing risks over time - Degli-Esposti, M (2019)
This thesis examines whether the risks associated with child maltreatment have changed over time in the UK; investigating changing risks at the societal and individual level. By adopting a unique socioecological approach, the thesis aims to determine whether: (a) the national incidence of child maltreatment has changed over the last 150 years, and (b) the impacts of child maltreatment on the risk of antisocial behaviour change across an individual’s life-course. The following methods were used to address these research aims and overcome challenges in child maltreatment research: multiple measures of child maltreatment, pre-existing sources of historical epidemiological data, observational study designs, and analytical methods that are sensitive to repeated measures (e.g. time series analyses, latent growth curve analyses). Research included developing a novel data source on the incidence of child maltreatment over time (iCoverT data source), examining long-term trends in child maltreatment from 1858 to 2016, and analysing 50 years of longitudinal data from the 1958 British birth cohort study. Results from examining societal risk over time showed that long-term trends in the incidence of child maltreatment have decreased since the 1850s. However, more recent trends have increased since 2000, especially for child protection registrations for emotional abuse and neglect. Results from examining risk across an individual’s life-course found that child maltreatment is associated with an increased risk of antisocial behaviour, with a persistent and stable association remaining up to 50 years old. Together, these findings demonstrate the long-lasting burden of child maltreatment at the societal and individual level. This thesis makes an important contribution to the literature by highlighting the role of time and epidemiological research methods in better understanding child maltreatment, and helps identify future directions for reducing the burden of child maltreatment.